ChemInform Abstract: Method for the Preparation of 4‐Aryl‐3‐pyrrolin‐2‐ones and Their 5‐Bromo Derivatives. Issue 20 (20th May 2014) - Vorona, M.; Orlova, N.; Kuznetsov, E.; Vikainis, S.; Liepinsh, E.; Belyakov, S.; Mishnev, A.; Veinberg, G.
Abstract via bromination‐dehydrobromination reactions of 1‐acetylpyrrolidone derivatives (I)